Lactobacillus for the treatment and prevention of atopic dermatitis: Clinical and experimental evidence - Xie, Anni; Chen, Ailing; Chen, Yuqing; Luo, Zichen; Jiang, Shanyu; Chen, Daozhen; Yu, Renqiang (Frontiers in Cellular and Infection Microbiology, 2023)
Atopic dermatitis (AD) is a chronic inflammatory skin disease, accompanied by itching and swelling. The main pathological mechanism of AD is related to the imbalance between Type 2 helper cells (Th2 cells) and Type 1 helper cells (Th1 cells). Currently, no safe and effective means to treat and prevent AD are available; moreover, some treatments have side effects. Probiotics, such as some strains of Lactobacillus, can address these concerns via various pathways: i) facilitating high patient compliance; ii) regulating Th1/Th2 balance, increasing IL-10 secretion, and reducing inflammatory cytokines; iii) accelerating the maturation of the immune system, maintaining intestinal homeostasis, and improving gut microbiota; and iv) improving the symptoms of AD. This review describes the treatment and prevention of AD using 13 species of Lactobacillus. AD is commonly observed in children. Therefore, the review includes a higher proportion of studies on AD in children and fewer in adolescents and adults. However, there are also some strains that do not improve the symptoms of AD and even worsen allergies in children. In addition, a subset of the genus Lactobacillus that can prevent and relieve AD has been identified in vitro. Therefore, future studies should include more in vivo studies and randomized controlled clinical trials. Given the advantages and disadvantages mentioned above, further research in this area is urgently required.